Multisensory Stimulation as Rebranding Strategy for Community Empowerment in CIDCO - Legia, Mariska (Universitas Multimedia Nusantara, 2025)
Creative Business of Diffable Community (CIDCO) is an inclusive art community that empowers children with disabilities through creative art practices. Despite its products' high aesthetic and social value, CIDCO faces challenges in building a consistent and emotionally resonant brand identity for the public. This study aims to formulate a multisensory rebranding strategy to enhance emotional bonds with the audience and increase awareness of the social values ​​carried. A descriptive qualitative approach is used through literature studies, participant observations, and in-depth interviews with CIDCO managers and audiences. SWOT analysis and TOWS matrix were utilized to map the community’s strategic position and to formulate key value propositions for redesigning its brand identity. The findings of this study offer a contribution to inclusive branding practices by integrating sensory and affective aspects in the context of community social entrepreneurship. Keywords: inclusive branding; multisensory experience; disability empowerment; social entrepreneurship